IMPLIKASI IMPLEMENTASI KEBIJAKAN DESENTRALISASI DAN OTONOMI DAERAH TERHADAP HUBUNGAN KEUANGAN PUSAT – DAERAH - to, Suryan (Pusjar SKPP Lembaga Administrasi Negara, 2006)
The Implementation of decentralization policy in Indonesia has been entering the second stage of governance reform, i.e. since the enactment of Law No. 32 and 33 of 2004. Undoubtedly, the whole stakeholders expect that the execution of regional autonomy would be much more rewarding in this period compared to the previous one (1999-2004). Highlight on two dimensions of decentralization are particularly required, those are, administrative decentralization and fiscal decentralization. This paper attempts to describe the implication of decentralization policy on the financial relationship between central and local government. The following crucial points are going to be discussed in this paper: future framework of decentralization and new structure of local government, stages of the implementation of regional autonomy, reform regarding central-local government relation, and internal-external implication of financial relationship between central and local government.Keywords: desentralisasi, otonomi daerah, hubungan keuangan Pusat-Daerah.